The Effectiveness of a Child-Centered Learning Approach as a Nursing Intervention in Improving Adolescents’ Knowledge about Early Marriage: A Quasi-Experimental Study - Wahyuningsih Wahyuningsih; Brajakson Siokal; Setiawan Kasim; Fhirawati Fhirawati; Sainah Sainah (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Early marriage remains a significant public health concern with adverse consequences for adolescents’ health, education, and psychosocial development. This study aimed to evaluate the effectiveness of child-centered learning Approach as a nursing intervention in improving adolescents’ knowledge regarding early marriage. A quasi-experimental study with a pretest–posttest control group design was conducted in Borongloe Subdistrict, Bontomarannu District, Gowa Regency. A total of 100 adolescents aged 15–18 years participated in the study and were assigned to either an intervention group (n = 50) and a control group (n = 50). The intervention group received health education based on a Child-Centered Learning Approach that emphasized active learner engagement, collaborative learning, critical thinking, problem-solving activities, and the use age-appropriate educational materials. The control group received conventional lecture-based health education. Adolescents’ regarding early marriage was measured before and after the intervention using a structured questionnaire. Data were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann–Whitney U test for between-group comparisons. The mean knowledge score in the intervention group increased from 55.44 to 87.00, while the control group showed only a slight change from 58.00 to 75.36. Statistical analysis showed a significant improvement in knowledge scores among adolescents in the intervention group after receiving child-centered learning–based health education (p < 0.001). In contrast, no significant change was observed in the control group. Comparative analysis between the two groups revealed a statistically significant difference in post-test knowledge scores (p < 0.001), indicating the effectiveness of the child-centered learning approach. These findings indicate that health education delivered through a child-centered learning approach can significantly improve adolescents’ knowledge regarding early marriage.